Experimental substantiation of methodic of 11-13 years old boxers` coordination development - Liu, Y. Q. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: experimental substantiation of methodic of junior boxers` coordination training. Material: in the research 18 boxers of 11-13 year old age participated. In total, during 4 months 42 trainings were conducted. Total time of coordination load`s fulfillment at each training was 15-45 minutes. Results: dynamic of results in control tests was statistically confident in the tested parameters of movements. It proves effectiveness of usage the tasks with complex-coordination orientation, accented on impact on sensor-informational and motor systems of movements in junior boxers` trainings. Conclusions: coordination training in boxing at initial stage shall include specialized varied means and methods, which would facilitate formation of motor condition and skills` basis. Motor condition and skills are a reserve for further rising of coordination abilities` level of junior sportsmen.